Controlling the cannibalism of African catfish juvenile by 17β‒estradiol hormone administration and the stocking density determination - Siregar, Khoirotun Nisa; Maulana, Fajar; Zairin Jr., Muhammad; Alimuddin, Alimuddin; Widanarni, Widanarni (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
An effort to increase the production of juvenile catfish is limited by the high mortality rate, especially caused by cannibalism. The hormonal treatment has been conducted as an effort to control cannibalism. This study used completely randomized factorial design, consisted of six treatments and three replications. There were two factors examined in this study, the first factor was different doses of 17β‒estradiol hormone (0, 30, and 60 mg estradiol‒17β/kg) incorporated in the feed, and the second factor was stocking density (150 and 300 fish/m2). Juvenile catfish with the size of 4.0 ± 0.1 cm were reared for 30 days in the 84 L aquarium. The results showed that hormone treatment could reduce cannibalism rate, type-I and II cannibalism compared to control (P<0.05). The results showed that the lowest of mortality was obtained in the treatment B (17β‒estradiol administration of 30 mg/kg, at stocking density of 150 fish/m2; P<0.05). The lowest cortisol level was found in treatment F, and the highest estradiol level was found in treatment F (17β‒estradiol administration of 60 mg/kg, at stocking density of 300 fish/m2; P<0.05). The lowest of blood glucose level was found in treatment B (P<0.05). The highest specific weight growth was found in the stocking density of 150 fish/m2 (P<0.05). The results of this study indicated that administration of 17β‒estradiol in feed could reduce the level of cannibalism in African catfish juvenile. Keywords: cannibalism, Juvenile, catfish, estradiol‒17β, cortisol ABSTRAK Upaya untuk meningkatkan produksi benih ikan lele dibatasi oleh tingginya angka kematian, terutama yang disebabkan oleh kanibalisme. Pendekatan hormonal telah dilakukan sebagai upaya pengendalian kanibalisme. Penelitian ini menggunakan rancangan acak lengkap faktorial, terdiri dari enam perlakuan dan tiga ulangan. Ada dua faktor yang diteliti dalam penelitian ini, faktor pertama adalah dosis hormon 17β‒estradiol yang berbeda (0, 30, dan 60 mg/kg) yang diberikan melalui pakan, dan faktor kedua adalah padat tebar (150 dan 300 ekor/m2). Benih ikan lele berukuran 4.0 ± 0.1 cm dipelihara selama 30 hari di akuarium (84 L). Hasil penelitian menunjukkan bahwa perlakuan hormon dapat menurunkan tingkat kanibalisme tipe‒I dan II dibandingkan kontrol (P<0.05). Hasil penelitian menunjukkan bahwa mortalitas terendah diperoleh pada perlakuan B (pemberian 17β‒estradiol 30 mg/kg, pada padat tebar 150 ekor/m2; P<0.05). Kadar kortisol terendah ditemukan pada perlakuan F, dan kadar estradiol tertinggi ditemukan pada perlakuan F (pemberian 17β‒estradiol 60 mg/kg, pada padat tebar 300 ekor/m2; P<0.05). Kadar glukosa darah terendah ditemukan pada perlakuan B (P<0.05). Pertumbuhan bobot spesifik tertinggi ditemukan pada padat tebar 150 ekor/m2 (P<0.05). Hasil penelitian ini menunjukkan bahwa pemberian hormon 17β‒estradiol dengan dosis 30 mg/kg pakan, dan padat tebar 150 ekor/m2 dapat menurunkan tingkat kanibalisme pada benih ikan lele di Afrika. Kata kunci: kanibalisme, juvenil, lele, 17β‒estradiol, kortisol